Comparative Study of STAD and Role-Playing Learning Methods in Indonesian Language Classes - Niken Vioreza; Nur Hasanah; Rena Sheila Selviani (S&Co Publishing, 2025)
This study aims to compare students’ learning outcomes using the STAD (Student Teams Achievement Divisions) model and the Role-Playing model in Grade III Indonesian language oral reading lessons at Madrasah Ibtidaiyah during the 2024/2025 academic year. A quasi-experimental design with a post-test-only control group was employed, involving two classes as samples: Grade III-A, taught using the STAD model, and Grade III-B, taught using the Role-Playing model, each consisting of 25 students selected through cluster random sampling. Data were analyzed using an independent sample t-test. The results revealed that the mean score of the STAD group was 83.28, while the Role-Playing group achieved a mean score of 78.44. The hypothesis test showed a significant difference between the two groups (tcalculated = 3.09 > ttable = 2.01, α = 0.05), leading to the rejection of H₀ and acceptance of H₁. These findings indicate that the STAD learning model is more effective than the Role-Playing model in enhancing students’ oral reading performance. The implication of this study emphasizes the importance of cooperative learning strategies like STAD in fostering active participation, collaboration, and deeper comprehension in Indonesian language learning.